POLYCYTHEMIA VERA AN EXAMPLE OF A CLINICAL CASE - Tomina, E. E.; Kamenskaya, E. P.; Lebedynets, P. V.; Tomakh, V. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The article concerns a clinical case management of patients with polycythemia vera. The data are given from the laboratory and instrumental diagnostic methods, clinical diagnosis, selection of the optimized treatment and modification of the habit of life.